Studi Pengamanan Kolom terhadap Konsep Perencanaan Struktur Tahan Gempa Ditinjau dari Peraturan SK SNI T-15-1991-03 ACI â€™99 dan Usulan MJN Priestly - Sunardi, Sunardi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
The development of anti-earthquake structure planning concept starts from planning structure based on force concept (forced based design), based on performance (performance based design) and develops the theory, which introduces and studies the anti-earthquake structure planning concept, which is based on movement (displacement - based), however, all of these element will return to the benefit principle of the building planning itself that is; instead giving safety value, the building construction also giving the safety for the users as well (user). This research is wished could giving either information about the column safety as a result of earthquake toward the planning structure based on force concept (forced based design), based on performance (performance based design) or introducing the planning structure based on displacement (displacement based design). The column safety as a result of earthquake is observed by the rule of SK. SNI T-15-1991-03 and the MJN Priestlyâ€™s suggestion. The result of this research is analyzing the rule, which is conducted in Indonesia that is SK.SNI.T-15-1991-03 and the MJN Priestlyâ€™s suggestion, which is concluded as follows: (A) the development of anti-earthquake structure planning concept (vibration), need special care especially in Indonesia by notice the politic security and globalization situation, (B) by noticing the rule of SNI, ACIâ€™99 and the MJN Priestlyâ€™s suggestion, there are 4 safety principles toward the column. The principles are as follows: (1) the tips of columns along the (lo) must be confined; (2) the column must be strong toward the friction failure (Vic) and stronger from elastic; (3) the column must be safe toward lateral bending (Sh); and (4) guaranteed structure by the philosophy â€œStrong column weak beamâ€, and (C) supporting the suggestion of Prof.Ir.Priyo Suprobo,MS.Ph.D and Ir. Faimun about the new approach suggestion for minimum confined requirement SK.SNI T-15-1991-03. At beam and column (1999). Lemlit ITS.Keywords: forced based design, performance based design, displacement based design, anti-earthquake column safety, minimum confined requirementPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3925[How to cite: Sunardi, 2005, Studi Pengamanan Kolom terhadap Konsep Perencanaan Struktur Tahan Gempa Ditinjau dari Peraturan SK SNI T-15-1991-03 ACI â€™99 dan Usulan MJN Priestly, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 96-105]